SYNTHESIS, IN SILICO STUDIES AND EVALUATION OF ANTIBACTERIAL ACTIVITY OF 4-SUBSTITUTED BENZYLIDENE-2-(PHENOXYMETHYL) OXAZOL-5(4H)-ONES - SHAHEEN BEGUM; ARIFA BEGUM SK; MANEESHA M; OME SHANTHI T; SATYA VARALAKSHMI D; MANJUSHA RK; BHARATHI K (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Arylidene-1, 3-oxazol-5-ones represent potential antibacterial agents. In the present work, a series of 4-substituted benzylidene-2- (phenoxymethyl) oxazol-5(4H)-ones were synthesized and screened for antibacterial activity against Gram-negative bacteria Escherichia coli. To explore plausible mechanisms, synthesized compounds were docked with DNA-Gyrase enzyme. Methods: All the reactants, phenoxy acetyl chloride, acetic anhydride, sodium acetate, substituted aromatic aldehydes, and glycine were triturated in a mortar by mechanical stirring. The antibacterial potentiality of the compounds was screened against E. coli using the disk diffusion method and the activity was recorded as a zone of inhibition. Results: Compound 2d, possessing 3, 4, 5-trimethoxy functionality on benzylidene ring exhibited the highest activity with 19 mm of the zone of inhibition which might be due to its higher interactions with DNA-Gyrase enzyme (ΔG-8.41 kcal/mol). Compounds 2a, 2b, and 2c exhibited moderate activity in the antimicrobial assay as well as in docking study indicating the positive contribution of substitution on benzylidene ring. Conclusion: A series of 4-substituted benzylidene-2-(phenoxymethyl) oxazol-5(4H)-ones were synthesized and evaluated for antibacterial activity. Compounds 2a, 2b, and 2c displayed moderate activity whereas 2d showed maximum zone of inhibition (19 mm). The good activity of these derivatives presumed to be due to the conformational flexibility of phenoxy methylene moiety which can be well accommodated in the target binding site.